Zooplankton community as an indicator of Arbekovsky Pond’s state (Penza) - V.A. Senkevich; T.G. Stoiko (Известия высших учебных заведений. Поволжский регион: Естественные науки, 2022)
Background. Urban ponds are subject to a strong anthropogenic load and, therefore, are always in the focus of attention of researchers. The pond at the clinical hospital No.6 in Penza was created in 1983. At the moment, cleaning measures are planned on this reservoir. Previously, for a long time (2010–2014), we have been studying the zooplankton community of Arbekovsky Pond. Due to the fact that large-scale work is expected in the reservoir, studies of these hydrobionts have been resumed.The purpose ofresearchistostudythe long-term and seasonal dynamics of the structural parameters of the zooplankton community in the Arbekovsky Pond and assess its condition before the start of cleaning measures. Material and methods. Samples for zooplankton research were taken in 2010– 2013 in May, early and mid-June, July and August (three samples each), in 2014 in May, July and August (nine samples each) and in 2020–2021. monthly from May to September (four samples each).A total of 139 samples were analyzed. Results. During seven years of research, 147 species and forms of zooplankton were recorded in Arbekovsky Pond.Of these, eleven taxa form a permanent species composition for 7 years of observations of the community.The species of rotifers Synchaeta kitina was recorded for the first time for the Penza region and replenished the complex of "northern invaders" in our region.The zooplankton community of the Arbekovsky Pond is sensitive to natural and anthropogenic impacts. The abundanceof species of the zooplankton community was the highest in hot and dry 2010, and the diversity of the community – in 2014, when its development was more calm and harmonious. In 2010–2014 Rotifers had a high abundance, and in 2020–2021 – copepods.Rotifers and copepods breathe through their entire body surface rather than through their gills, so they can more successfully withstand hypoxia.The structural parameters of the zooplankton community in recent years indicate the accumulation of organic matter in the water and the violation of the oxygen regime in the pond. Conclusions.The results of the study of the current state of the zooplankton community of the Arbekovsky Pond confirm the need for cleaning this reservoir with subsequent regulation of the hydrological regime.